2015
DOI: 10.1007/s00521-015-2062-1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of local scour around bridge piers using the ANFIS method

Abstract: Local scour around bridge piers is a complicated physical process and involves highly three-dimensional flows. Thus, the scour depth, which is directly related to the safety of a bridge, cannot be given in the form of the exact relationship of dependent variables via an analytical method. This paper proposes the use of the adaptive neuro-fuzzy inference system (ANFIS) method for predicting the scour depth around a bridge pier. Five variables including mean velocity, flow depth, size of sediment particles, crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…bridge piers [50]. The authors reported better modeling performance using the dimensional variables over the normalized variables.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…bridge piers [50]. The authors reported better modeling performance using the dimensional variables over the normalized variables.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, it proves that the dimensional analysis helps to substantially ameliorate the modeling results as confirmed in previous studies. Recalling the literature, artificial neural network and adaptive neuro-fuzzy inference system models were established to predict scour depth around bridge piers [50]. The authors reported better modeling performance using the dimensional variables over the normalized variables.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After collision of bodies, their new positions and velocities are updated based on Eqs. (10)(11)(12)(13).…”
Section: Fig 2 Collision Of Bodiesmentioning
confidence: 99%
“…The results showed that the most important parameters affecting relative scour depth (d s /y) included ratio of pier width to flow depth (D/y) and ratio of pier length to flow depth (L/y). In addition, other researchers have performed a number of studies in this field as well, such as references [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%